Prevalence of Nosocomial Infections in Hebron- Palestine Hospitals - Salah, Muna (Journal of Advances in Medicine and Medical Research, 2017)
Background: Nosocomial infections, especially urinary tract infections, form a serious problem in hospitals, and are associated with increased mortality, morbidity, and prolonged hospital stay. In addition, the most infection rates occur at neonatal intensive care units (NICUs). Aims: To investigate the prevalence of urinary tract infections in different clinical departments and to screen for the main pathogens that colonize and cause infection in infants in the NICU in order to provide a scientific basis for effective prevention and control systems for nosocomial infections. Methods: This cross sectional study was conducted in three hospitals in Hebron. 81 urine samples were collected from the different clinical departments at the hospitals, and 79 swab samples from the throat, umbilical cord, nose, and eye were collected from neonates who were admitted to theNICU section in the three studied hospitals. All samples were cultured on Mac Conkey and human blood agar, and positive cultures were identified according to their morphology, gram stain, motility, and biochemical tests. Antibiotic susceptibility testing was performed using Kirby-Bauer’s disk diffusion method and interpreted according to Clinical & Laboratory Standards Institute guidelines 2016. Results: Results from collected urine samples showed that 20% of patients carried infectious bacteria. Enterobacteriaceae pathogens were the most common in addition to Staphylococcus aureus, with 22% of Enterobacteriaceae isolates being Extended Spectrum β-lactamase (ESBL). Screening in NICU departments showed that infections were reported in 77.2% of samples, of which coagulase negative Staphylococcus formed 50%, Enterobacteriaceae formed 42%, and S. aureus formed about 8% of the isolated pathogens. Almost 58% of the Enterobacteriaceae were ESBL producing, and all S. aureus isolates were methicillin resistant S. aureus (MRSA). Conclusions: The data collected point to a high threat of healthcare associated infections in the hospitals studied and to the urgent need to establish effective infection control systems in Palestine based on standardized surveillance.
Keywords: Nosocomial infections; neonatal intensive care unit; urinary tract infections; healthcare associated infections, Palestine hospitals.